The Role of Gilani Businessmen and Artists in Propagation of Relations between Iran and India - Azmodeh, Seyed Abbas (Journal of History Culture and Art Research, 2017)
One of the places where Gilani people have been a wide settlement is India subcontinent. Since they found India as a safe place for themselves, they migrated to there and have eventually reached to high religious and political growth. Fertile lands of India with unlimited treasures were a motive for migration of famous Gilanies faces such as Abdulrashid Deylami and Ali Gilani to India. However, the chaos during the reign of Mongolians, Turkmens and Safavies resulted into the extinction of Gilani throne. The author in this article through analytic-descriptive method tries to show the provided services by Gilanies immigrant to India that caused into extending of Iranian art, and also political and business relations between both countries.